A mediated multigroup model examining marijuana use consequences by sexual orientation in us college students. (December 2018) - Parnes, Jamie E.; Prince, Mark A.; Conner, Bradley T.; ,
Abstract: Marijuana use holds a curvilinear relation to sexual orientation, whereby bisexual individuals reporter higher frequency of use than exclusively hetero- or homosexual individuals. This relation differs by gender, with more pronounced differences among women. Bisexual individuals are at greater risk for negative consequences of marijuana use, such as dependence. To mitigate potential risks, individuals employ protective behavioral strategies (PBS). While differences in use are known, research has yet to examine if consequences and PBS use vary by sexual orientation. This study seeks to address the relations between sexual orientation, consequences, gender, and PBS. It was hypothesized that orientation would be associated with consequences, mediated by PBS, and these relations would vary by gender. College students ( N  = 8141) from 11 different universities completed an online survey measuring marijuana consequences, PBS use, and sexual orientation. A final analytic sample ( n  = 2091) was composed of participants who indicated past 30-day marijuana use (60% women, 64% White, mean age 19.92). Path analysis was used to test all study hypothesis. Results indicated a curvilinear relation between sexual orientation and consequences among men, however not women. Moreover, PBS use mediated the relation between orientation and consequences among men, and negatively predicted consequences among women. Conclusions include that mixed sexual orientation men experience higher consequences through lower PBS use. For women, PBS use buffers against consequences. These findings reflect a general effectiveness of PBS use for mitigating negative marijuana-related consequences. The implications of these results are discussed. Highlights: We examined how sexual orientation relates to marijuana-related consequences. We studied how sexual orientation relates to consequences for men and women. Protective behavioral strategies mediate sexual orientation and use consequences. Protective behavioral strategies are promising for harm reduction interventions. Understanding unique aspects of men's experiences may best inform interventions.